Political Corruption and Electoral Systems Seen with Economists’ Lenses - Dzionek-Kozłowska, Joanna (Annales. Etyka w Życiu Gospodarczym, 2014)
The ongoing process of democratisation lead to the growing importance of the electoral systems that regulate the procedures of gaining and legitimizing power in democracy. Taking it into account it is worth asking about the relationship between these particular ‘game rules’ contained into electoral law and the respect of the rule of law, being one of the basic norms of a democratic system. A question then may be raised about the existence and the character of the relation between electoral systems and the level of political corruption. It is worth noticing that besides the research conducted by political scientists and the representatives of various branches of social sciences the significant analysis of the issue have been presented by the economists. In this article a brief overview of the economic studies on the relationship between level of political corruption and the electoral systems is presented so as to assess to what degree this approach may be treated as fruitful.